Unlimited Liability and Law Firm Organization: Tax Factors and the Direction of Causation - Gilson, Ronald J. (Journal of Political Economy, 1991)
In a recent issue of this Journal, Carr and Mathewson (1988) test a model of the impact of limited and unlimited liability regimes on the nature of firms by comparing the performance of law firms operated as partnerships and sole proprietorships (and therefore subject to unlimited liability) with that of law firms operated as corporations (and therefore subject to limited liability).' In their model, "unlimited liability by raising the cost of ownership rights discourages investment in the firm, causing legal firms to be inefficiently small" (p. 779). The peculiar history of organizational form in the legal profession seemed to provide an opportunity to test their model's prediction. Prior to the 1960s, state law prevented law firms from incorporating, with the effect that unlimited liability was mandated. During the 1960s and early 1970s, a large number of states passed statutes that allowed law and other professional service firms to incorporate, thereby giving such firms the option to elect either an unlimited or a limited liability regime. The result was a universe that included some law firms that were subject to unlimited liability and some that were subject to limited liability.